PREVALENSI STATUS GIZI PADA SISWA-SISWI SMK N PRINGKUKU KABUPATEN PACITAN - Novian Wely Asmoro; A.I. Niken Tari; Afriyanti . (Pro Food, 2017)
School-aged teenagers, in particular, have a habit and the pattern of food consumption is often irregular and does not pay attention to the pattern of good and balanced consumption. The condition of unbalanced consumption patterns can affect individual nutritional status. Body mass index measurement (BMI) is related to the prevalence of nutritional status in students of SMK N Pringkuku Kab. Pacitan is used as a general description of nutritional conditions within the school environment. Nutrition status data obtained from the calculation of height and weight and then calculated body mass index (BMI), and data related to healthy habits and lifestyle obtained from the filling of questionnaires by respondents. The results showed that there were students with less nutritional status, normal nutritional status, more nutritional status, and obesity were 25.44%, 58.18% 10.91% and 5.45% respectively with the condition related to sex and general breakfast habits and the frequency of eating a day showed 72.09% of students behaved well, while 27.91% of students behaved eating is not good. Keywords: body mass index, consumption patterns, nutrition, students ABSTRAK Remaja usia sekolah khususnya memilikikebiasaan dan pola konsumsi makanan sering tidak teratur serta tidak memperhatikan pola konsumsi yang baik dan seimbang. Kondisi pola konsumsi yang tidak seimbang dapat berpengaruh pada status gizi individu. Pengukuran body mass index (BMI) terkait dengan prevalensi status gizi pada siswa SMK N Pringkuku Kab. Pacitan digunakan sebagai gambaran umum kondisi gizi dilingkungan sekolah. Data status gizi diperoleh dari perhitungan tinggi badan dan berat badan kemudian dilakukan perhitungan body mass index (BMI), dan data terkait kebiasaan-kebiasaan dan pola hidup sehat diperoleh dari pengisian kuisoner oleh responden. Hasil penelitian menunjukan terdapat siswa dengan status gizi kurang, status gizi normal, status gizi lebih dan obesitas berturut-turut sebanyak 25,44%, 58,18% 10,91% dan 5,45% dengan kondisi tersebut berhubungan dengan jenis kelamin serta secara umum kebiasaan sarapan pagi dan frekuensi makan dalam sehari menujukan 72,09% siswa berperilaku makan baik, sedangkan 27,91% siswa berperilaku makan tidak baik. Kata kunci : body mass index, gizi, pola konsumsi,siswa